Total Factor Productivity Estimation in Manufacturing Sector of Odisha - Jena, Duryodhan; ., . (International Journal of Engineering and Technology, 2018)
Manufacturing sector aimed at an efficient and technologically developed industry with a view to boosting country’s level of competitiveness through a rise in productivity. Thus, productivity explains the relationship between production and means of production. Growth of efficiency in manufacturing sector has been assessed on the basis of Total Factor Productivity (TFP) index. In this paper, an attempt has been made to estimate the TFP of manufacturing sector of Odisha over the decades. The findings of the study revealed that the productivity index is more than 100 for most of the years indicating the growth in the manufacturing sector. The TFP index reached the highest level i.e. about 200 in the year 2004-05.